Analisis Sumber Daya Insani bagi Perkembangan Perbankan Syariah di Indonesia dengan Metode Systematic Literature Review - Kabeakan, Nurbaiti Rizki; Zainarti, Zainarti; Nasution, Annio Indah Lestari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to determine the development of Islamic banking in Indonesia, the development of human resource competencies in Indonesian Islamic banking, and the role of human resource competencies for the development of Islamic banking in Indonesia. This type of research is a Systematic Literature Review (SLR), which is a method that is systematic, clear, comprehensive, identifies, analyzes, assesses, evaluates, and interprets all findings on a research topic (research question). Sources of data as subjects and objects come from indexed journal literature that has ISSN (International Standard Serial Number) electronically published via the internet with the code E-ISSN. Data collection was done through internet surfing from Google Scholars. The results of the study stated that the results of the Systematic Literature Review of all research contained in journals that have been published since 2014 to 2021 confirm that the competence of human resources in Indonesia is still low both at the level of quality and quantity which causes the weak performance of Islamic banking. competence of human resources in Islamic banking in Indonesia, among others, because the recruitment, selection and placement of employees are not in accordance with their expertise, mastery of muamalah fiqh theories and law of engagement are lacking, and there is no ability to modify banking products combined with sharia principles. Islam. The solutions given to answer the problem of the low competence of human resources in Islamic banking in Indonesia above include better recruitment, selection and placement of human resources correctly according to the right job, paying close attention when recruiting really competent people from both sides. in terms of sharia and finance, and increasing the role of universities, especially Islamic universities, to provide quality human resources.